Implementation of Wadiah Agreement on IB Makbul Hajj Savings at PT Bank Sumut Syariah Katamso - Novidia Utami; Ahmad Perdana Indra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
Bank Sumut Syariah Katamso, which is a bank that collects and distributes funds to the public, through several products including the Hajj savings account iB Makbul. In carrying out its activities, namely raising funds, of course, banks need a strategy to attract customers to open iB Makbul Hajj savings at Bank Sumut Syariah Katamso. The purpose of this study was to determine the management of the iB Makbul Hajj savings product at the Katamso Syariah Bank Sumut, namely to determine the application of the iB Makbul Hajj savings product at the Katamso Syariah Sumut Bank and to find out the obstacles and obstacles faced in implementing the iB Makbul Hajj savings product at the Katamso Syariah Sumut Bank. . The results of the study show that Bank Sumut Syariah Katamso applies the type of Hajj savings product iB Makbul which uses a product with the principles of deposit (wadiah yad adh-dhamanah), namely an agreement in which the recipient of the deposit can use the deposited item with permission to guarantee and guarantee to return the deposit. in its entirety at any time when the owner wishes it. From this study, it was concluded that Bank Sumut Syariah Katamso applied the iB Makbul Hajj savings product using a wadiah yad adh-dhamanah contract for savers, Hajj savings management was by opening a Hajj savings account, making a health certificate, filling out a registration letter to go for Hajj at the Ministry of Religion office. , payment at the bank, reported to the office of the Ministry of Religion, payment of the costs of organizing the pilgrimage (BPIH).